A review on co-cultivation of microalgae with filamentous fungi: Efficient harvesting, wastewater treatment and biofuel production. (April 2021) - Chu, Ruoyu; Li, Shuangxi; Zhu, Liandong; Yin, Zhihong; Hu, Dan; Liu, Chenchen; Mo, Fan
Abstract: As the third generation biofuel feedstock to confront with energy crisis, microalgae have great potential for the exploration of renewable energy fields, whereas the high cost related to biomass production and harvesting is the main bottleneck to hinder the applications on a large scale. To mitigate the environmental impacts in a sustainable mode, co-culturing filamentous fungi with targeted microalgae is a superior method to efficiently accumulate and harvest the total biomass. This paper serves as a base to review current advances in pelletization of microalgae with fungi for the co-cultivation process. The pellet formation is initially introduced, and then electrostatic interactions, hydrophobic interactions and specific components on cell walls as the main harvesting mechanisms are explored and generalized together with the inclusion of critical affecting parameters for efficiency promotion. Apart from the discussion about biomass harvesting, the latest studies of this co-cultivated technology on wastewater treatment in diverse types associated with corresponding removal mechanisms are analyzed as well. Subsequently, this article emphasizes the effects of fungal-algal cultivation on downstream processing for biofuel production, followed by the practical bioenergy conversion performances. Based on the policies support, the implications of this novel co-cultivation technology have shown the potential in further development. Meanwhile, the current challenges and future perspectives about harvesting on a large scale, removal of multiple pollutants and exploration of integrated biorefinery are pointed out systematically. Graphical abstract: Image 1 Highlights: Filamentous fungi can entrap microalgae to form co-pellets. Co-cultivation achieves high efficiency in biomass harvesting. Pollutants in wastewater are efficiently removed by fungal-algal pellets. Filamentous fungi may cause positive effects on the total biofuel production. Fungal-algal pellets have enhanced the feasibility on large-scale applications.